Analisis Semiotika Pesan Dakwah dalam Novel Dua Barista Karya Najhaty Sharma - Mutiatussholikah, Dita; Setyawan, Agus; fidhoh, kha (Journal of Communication Studies, 2023)
Da'wah can be done by anyone, anytime, and anywhere with the abilities and knowledge they have. Da'wah has various ways or methods. one of them is through novels. So the researcher decided to examine the message of da'wah in the novel Dua Barista by Najathy Sharma. This novel is interesting and worth researching because it is an Islamic genre novel which contains many preaching messages. The problem formulation of this research is: What are the signifiers and signifieds contained in the novel Dua Barista by Najhaty Sharma? And what is the message of da'wah in the novel Dua Barista by Najhaty Sharma? The aim of this research is to determine the signifiers and signifieds in the novel Dua Barista by Najhaty Sharma and explain the message of da'wah contained in the novel Dua Barista by Najhaty Sharma. This type of research uses a qualitative approach to semiotic analysis. Data analysis in this research uses Ferdinand De Saussure's semiotic method with two stages, namely signifier and signified. Based on the research that has been conducted, the markers for this research were taken from a novel conversation between two baristas. In it there are signs contained in the novel Dua Barista by Najathy Sharma, namely: Gratitude, Courtesy, Justice, Faith, Patience, Sincerity, Worship, Saving disgrace, Backbiting, Husnudzon, Endeavor, Guyub rukun, and Affection, the message of accusation in the novel Dua Barista namely Aqidah, Morals, and Sharia.